Synthesis and Characterization of Ordered Intermetallic Nanostructured PtSn/C and PtSb/C and Evaluation as Electrodes for Alcohol Oxidation - da Silva, Marcelo Rodrigues [UNESP]; Dias Angelo, Antonio Carlos [UNESP] (Springer, 2010)
Ordered intermetallic compounds of Pt-based metal electrocatalysts have been recently proposed as very efficient anode materials for reactions involved in low temperature fuel cells. In this work, supported ordered intermetallics nanoparticles PtSn/C and PtSb/C and supported platinum nanoparticles (Pt/C) were prepared at low temperature from their metallic precursors by a modified polyol process, using tetraethylene glycol as the solvent and reducing agent and Vulcan carbon XC-72 as the support. Powder X-ray diffraction patterns confirmed the presence of the ordered intermetallic phase and furnished lattice parameters and crystal structure. Transmission electron microscopy images show that the metal particles were highly dispersed and distributed homogeneously over the support, and energy-dispersive X-ray spectroscopy showed that the composition of the final product is within that of the desired stoichiometry. The electrocatalytic activity of these intermetallic phases toward the oxidation of methanol, ethanol, and ethylene glycol were confirmed by cyclic voltammetry and steady-state polarization curve at room temperature. The results showed that the supported intermetallic nanoparticles PtSn and PtSb are more active than the Pt/C catalyst prepared by the same method for alcohol oxidation.
Keywords: Ordered intermetallic phase; Nanoparticles; Polyol; Electrocatalytic activity